DEveloping a Complex Intervention for DEteriorating patients using theoretical modelling (DECIDE study): Study protocol. (17th June 2019) - Smith, Duncan; Francis, Jill J.; Aitken, Leanne M.
Abstract: Aim: To develop a theory‐based complex intervention (targeting nursing staff), to enhance enablers and overcome barriers to enact expected behaviour when monitoring patients and responding to abnormal vital signs that signal deterioration. Design: A mixed method design including structured observations on hospital wards, field notes, brief, unrecorded interviews and semi‐structured interviews to inform the development of an intervention to enhance practice. Methods: Semi‐structured interviews will be conducted with nursing staff using a topic guide informed by the Theoretical Domains Framework. Semi‐structured interviews will be transcribed verbatim and coded deductively into the 14 Theoretical Domains Framework domains and then inductively into "belief statements". Priority domains will be identified and mapped to appropriate behaviour change techniques. Intervention content and mode of delivery (how behaviour change techniques are operationalized) will be developed using nominal groups, during which participants (clinicians) will rank behaviour change techniques/mode of delivery combinations according to acceptability and feasibility. Findings will be synthesised to develop an intervention manual. Discussion: Despite being a priority for clinicians, researchers and policymakers for two decades, "sub‐optimal care" of the deteriorating ward patient persists. Existing interventions have been largely educational (i.e. targeting assumed knowledge deficits) with limited evidence that they change staff behaviour. Staff behaviour when monitoring and responding to abnormal vital signs is likely influenced by a range of mediators that includes barriers and enablers. Impact: Systematically applying theory and evidence‐based methods, will result in the specification of an intervention which is more likely to result in behaviour change and can be tested empirically in future research. Abstract : 目的: 开发基于理论的综合干预措施(目标群体为护士), 为监控患者以及对病情恶化异常生命体征做出反应过程中实施预期行为提高动力, 克服障碍。 设计: 混合方法设计包括医院病房结构化观察、现场记录、不记录简短访谈以及半结构化访谈, 这些方法可以告知干预的进行过程, 从而加强操作。 方法: 半结构化访谈将通过理论域框架下话题指导的形式在护士中开展。半结构化访谈内容将被逐字转录并演绎编码为理论域框架中的14个域, 随后归纳编码为"简短的陈述"。确定优先域并将其映射到行为变化技巧中。 采用团体列名法确定干预内容及传递形式(即行为变化技巧的运用方式), 参与者根据可接受度及可行性对行为变化技巧/传递组合形式进行评级。综合各项发现, 编制成干预手册。 讨论: 虽然二十年来这种干预措施优先在临床医生、研究者、决策者中使用, 但恶化患者的 "次优护理"也一直使用这项措施。目前的干预措施由于证明自身可改变医疗人员行为的证据有限, 因而大多只具备教育意义(例如, 指向目前的知识缺陷)。监控及对异常生命体征信号做出反应时医疗人员的行为可能受阻碍因素、动力因素等多种因素影响。 影响: 系统地应用理论法以及基于证据的方法将使得干预措施的规范化, 更大可能致使行为变化, 并且这种方法可在未来的研究中进行经验测试。